A reconsideration of the relationship between town size and well-being in Latin America - Antje Jantsch; Alan Piper (Applied Research in Quality of Life, 2026)
In this study, we explore the relationship between town size and subjective well-being (SWB) in Latin America. We utilize data from the Latinobarómetro survey from 2005 to 2015, employing multilevel modeling to analyze individual responses to life satisfaction as an indicator of SWB. We refine the town size categories provided in the Latinobarómetro by cross-referencing the geographic information with the United Nations Demographic Yearbook, one of our main contributions, leaving us with more refined town size categories than previous research. Given previous theories, we also explore how education moderates the town size-SWB relationship. Our findings reveal that individuals in towns with populations between 10,000 and 500,000 report lower life satisfaction compared to those in smaller or larger towns. Controlling for national macroeconomic conditions reverses the positive association between SWB and living in a very large city. Furthermore, we find some support for the notion that highly-educated individuals are more satisfied than the low-educated in large cities. This study comprehensively underscores the importance of refining town size data and suggests avenues for future research to deepen collective understanding of the `geography of happiness' in Latin America.
Keywords: 630; life satisfaction; subjective well-being; education; town size; Latin America; Latinobarómetro; multilevel modelling